A elephant war scene from the Mahabharat, showing Arjuna (wearing a crown) with his famous bow, Gandiva, while Bhim wields his mace - Brig. Ajai Singh (2021)
Image courtesy: Brig A.P. Singh - www.collectingmoments.in